Democracy in New Media: The Influence of Interactive Media on the Changes in Politics and Public Communication - Siudak, Martyna Małgorzata (Media - Culture - Social Communication, 2019)
With the emergence of the Internet, alongside the traditional mediasphere consisting of press, radio and television, a new reality came to be – the network reality. Developing teleinformatic technologies have had an impact on the changes occurring in the sphere of social communication. The aim of the author of this article is to present the transformations taking place especially in the subsystem of public communication, including the world of politics. New media effectively influence the changes in the flow of information between authorities and media or between authorities and the citizens. Their interactive character has the power to change the politics or political campaigns. A question emerges: is it justified to include the new media in the democratic system? The behaviour of politicians, officials and citizens often shows that it has already happened (although in a non-formal way).